Juxtaposition, repetition, dance - Sônia Salzstein (ARS)
Abstract This essay, approaching Richard Serra’s works exhibited at Instituto Moreira Salles in Rio de Janeiro, in 2014, discusses the remarkable interplay between sculpture and drawing in the artist’s production, this interplay having frequently resulted in drawings marked by such sculptural qualities as solidity, mass, weight, lightness, fluidity and, converselly, in sculptures and installations addressing architectural and structural issues. The text also points out to the cezannesque procedure which mark several drawings of Serra, where two dimensional surfaces usually basculate in steep angles, favouring a continuous switching back and forth between horizontals and verticals, flat and receding planes. From this relationship to drawing, as is argued, derives the crucial role gestures and action on materials play in this work, assigning to it a bodily plasticity.